Meninos brincam de bola e meninas brincam de bola também: problematizando a dominação masculina no futebol nas aulas de Educação Física - Perassolli, Marina Arriaga (Universidade Federal de São Carlos, 2025)
This research takes as its starting point the male domination in the practice of soccer (football) inside and outside the school environment. With four decades of prohibition on women's participation in sports, and more specifically in soccer, the consequences of this impediment are still found, and the invisibility of women's participation promotes acts of prejudice and sexism during Physical Education classes. It is necessary, therefore, to work on soccer in schools beyond the reproduction of the spectacularized sport logic, understanding this sport as a cultural phenomenon that carries countless possibilities and knowledge. We seek, then, with this research to identify and analyze the educational processes emerging from the implementation of a didactic unit of soccer composed of 12 classes with a 5th-grade elementary school class during Physical Education classes. A qualitative research of the action-research type was carried out, in which the main data collection instrument was field notes and questionnaires that were analyzed through content analysis using the category coding method. The results and their analysis are divided into categories, the first of which is “Boys don't want to play with girls because they are worse,” which brings sexist situations that occurred throughout the application of the classes and their developments. The second is entitled “When I scored the goal, I saw that I can actually play soccer or do something else,” and brings evidence about the process of empowerment and confidence of the girls. The third, entitled “We don't know any female athletes, that's why we didn't talk,” discusses the educational processes that emerged from factors of the external logic of soccer. We consider that the application of the didactic unit provided students with several positive experiences and an increase in girls' confidence regarding their participation in sports activities and soccer, in addition to having provided students with various knowledge related to the external logic of soccer."
Boys play with balls and girls play with balls too: problematizing male domination in football in Physical Education classes
Keywords: Educação Física; Futebol; Gênero; CIENCIAS DA SAUDE::EDUCACAO FISICA